Perancangan Sistem Informasi Perkembangan Akademik Online Taman Kanak-Kanak Pada Smartphone Berbasis Android - Joash Lorenzo Imbenay; Yulianus Palopak (Fakultas Teknologi Informasi - Universitas Advent Indonesia, 2017)
The use of a smartphone as a device access to information was growing very rapidly. Moreover, many mobile applications were created to make the required information easily accessible. Not only as a device for communication, but had been converted to a device that facilitates the work of human kind. Smartphones with Android operating system had advantages with fast internet access but the price is relatively cheap when compared to other smartphones. These advantages make the various parties competing to develop applications on the Android operating system, was no exception with the Online Information System for The Grades of Kindergarten. Authors used Android technology for designing Grades Information System Online on Android-based smartphone. With this application, users no longer need to open System Information Online Grades kindergarten in the browser with the support of computers, but only by using a smartphone based on Android. The purpose of this study is to easily provide information on the results of learning outcomes of students from the school to parents or guardians of students. The methodology used in this research is Waterfall method, where author analyzes requirements, design the system, making the system, test the system, and implementing the system. This application is built using Android Studio as an IDE (Integrated Development Environment). For communicating with the database server, this application used the JSON Parse as a bridge to exchange data with the database server. Broadly speaking, the application had been able to go well as access to student data, teacher data, daily reports, report cards and change the password of the user. However, this application still needs to be developed in parts of the user interface and development on various platforms other than Android.